KORELASI KECERDASAN EMOSIONAL DENGAN KETERAMPILAN PADA PEMBELAJARAN PENDIDIKAN JASMANI - Akbar, Andi Khemal (Atta'dib Jurnal Pendidikan Agama Islam, 2023)
Â The main problems of this study are: 1) What is the emotional intelligence of fifth-grade students at MI At-thahiriyah Componge, Awangpone District, Bone Regency? 2) What is the dribbling skill of fifth-grade students at MI At-thahiriyah Componge, Awangpone District, Bone Regency? 3) Is there a significant correlation between emotional intelligence and dribbling skills in Physical Education learning for fifth-grade students at MI At-thahiriyah Componge, Awangpone District, Bone Regency? The research method used in this study is quantitative research. The population of this study is fifth-grade students. The sample is all fifth-grade students with a total of 23 students. The research instruments used were questionnaires, observations, and documentation. The data analysis techniques used were descriptive statistical analysis, product moment analysis, and simple linear regression equation analysis. Based on the results of data analysis using descriptive statistics, it is known that the average value for the emotional intelligence variable (X) is 35.35, the number 35.35 is in the range of 34-37 with the category of quite good. The average value for the dribbling skill variable (Y) is 38.17, the number 38.17 is in the range of 35-38 with the category of quite good. While the calculation results to find the correlation of emotional intelligence with dribbling skills obtained the value of rxy = 0.35. This indicates that the correlation of emotional intelligence with dribbling skills has a positive correlation. The interpretation of the correlation coefficient value (rxy) proposed by Sugiyono, the score is in the range of 0.20-0.399 which has a low level of relationship. The results of the significance test showed the results of ttable<tcount with a value of 1.323 < 1.71 with the regression result of Y' = 25.4 + 0.36. Therefore, it can be concluded that this study found a positive and significant correlation between emotional intelligence and dribbling skills.Keywords: Emotional Intelligence, Dribbling Skill, Physical Education.